Mengajar Bahasa Inggris di SD/AWP Rsi Markandya Taro di Desa Taro - Ni Made Ernila Junipisa; Laras Oktaviani; I Wayan Nugraha (Pubfine Media Group, 2024)
English is an international language spoken in many countries around the world. The ability to speak English can open up many opportunities for children in the future, such as expanding career and study abroad opportunities, as well as broadening horizons and knowledge about the world. English has also become the language of instruction in many fields, such as technology, business, and science. Learning English early on can help children acquire better language skills in general, including the ability to understand correct grammar and sentence structure which directly improves the ability to communicate effectively using English, both orally and in writing. The method used in this program starts from preparing teaching materials in the form of Power Point and animated videos, and providing quizzes in accordance with the material that has been taught so that it can attract students to learn English. The material taught is how to read and write alphabet, number, color, fruit, animals, and self-introduction in English in grades 2 and 3 of SD / AWP Rsi Markandya Taro can be carried out well and in accordance with expectations. This is proven by the achievement of all the material that has been taught to students at SD / AWP Rsi Markandya well, the teachers are also very enthusiastic in providing assistance in the form of material for work programs implemented by KKNT participants. Although there are few obstacles in the teaching process, all can be overcome with good enthusiasm and cooperation by KKNT members and support by the Principal and Teachers.